Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Connect with a community of experts ready to provide precise solutions to your questions on our user-friendly Q&A platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Answer:
The solution to the equation is as follows;
[tex]x = \frac{5}{19} ,\ and \ y= \frac{2}{19}[/tex]
Step-by-step explanation:
Given;
5x - 3y = 1
3x + 2y = 1
Solving both equation simultaneously;
2: 10x - 6y = 2
3: 9x + 6y = 3
--------------------------
19x + 0 = 5
x = 5/19
substitute the value of x in any of the equations above and solve for y;
5x - 3y = 1
5 (5/19) - 3y = 1
25/19 -3y = 1
[tex]3y = \frac{25}{19} -1\\\\3y = \frac{25-19}{19} \\\\3y = \frac{6}{19} \\\\y = \frac{2}{19}[/tex]
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.